Phenotypic and genetic investigation of plant phenological development, architecture and yield in winged bean (Psophocarpus tetragonolobus (L.) DC.) - Chong, Yuet Tian (2025)
The worsening effects of climate change and malnutrition have significantly impacted global food and nutrition security. Diversifying food sources through the cultivation of underutilised crops could mitigate these challenges and promote resilient agricultural food systems. Winged bean (Psophocarpus tetragonolobus (L.) DC.) is a protein-rich crop grown in humid tropical regions. With its various edible plant parts, broad distribution in the tropics, and adaptation to diverse local environmental conditions, it has notable trait variations for exploration in crop improvement. Research on winged bean genetic diversity has been limited in the past 50 years, primarily relying on phenotypic assessments without the utilisation of molecular markers. However, recent advancements in genotyping techniques have enabled the integration of phenotypic and genetic data. Molecular breeding accelerates the characterisation of diverse core collections, leading to cultivar development, contributing to global initiatives for dietary diversity and nutritional resilience.